107k views
4 votes
Consider the following equation-3/2x + 12 = 2x - 3Approximate the solution to the equation above using three iterations of successive approximation. Use the graph below as a starting point

1 Answer

5 votes

the initial equation is:


-(3)/(2)x+12=2x-3

now we simplify the equation:


\begin{gathered} 2x+(3)/(2)x-3-12=0 \\ (7)/(2)x-15=0 \end{gathered}

User Sandburg
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.